1984
DOI: 10.1177/002580248402400210
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Stature from Parts of Ulna and Tibia

Abstract: 113 SUMMARYOne hundred and sixty four right and 187 left, dry, fully ossified human ulnae have been studied to derive regression formulae for the establishment of the total length of the ulna from the upper and lower segments, the line of division between the segments being the lowest level of insertion of the brachialis muscle.Also, 175 right and 179 left, dry, fully ossified tibiae have been studied to derive regression formulae for establishment of the total length of the tibia from the upper and lower segm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0
1

Year Published

2001
2001
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 2 publications
0
11
0
1
Order By: Relevance
“…Also, when thewhole of the long bones becomes unavailable in many situations, some methods have been employed for the usefulness of the fragments of long bones such as radius and femur (Mysorekar et al, 1980), femur and tibia (Steele & Mckern), ulna and tibia (Mysorekar et al, 1984) and humerus (Wright & Vasquez). So, by knowing the measurements of different segments of the humerus, based on their articular surfaces and muscle attachments, total length of the humerus can be determined (Muñoz et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Also, when thewhole of the long bones becomes unavailable in many situations, some methods have been employed for the usefulness of the fragments of long bones such as radius and femur (Mysorekar et al, 1980), femur and tibia (Steele & Mckern), ulna and tibia (Mysorekar et al, 1984) and humerus (Wright & Vasquez). So, by knowing the measurements of different segments of the humerus, based on their articular surfaces and muscle attachments, total length of the humerus can be determined (Muñoz et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have shown that regression equations derived for stature estimation from intact long bones of the upper and lower extremities are accurate [14][15][16][17][18][19]; however, these equations are both population and sex specific [15,20]. Since intact long bones are not always available for forensic analysis, other researchers have used fragments of long bones for stature estimation with various degrees of success [21][22][23][24]. In South Africa, regression equations have been derived for stature estimation from measurements of intact long bones of the upper and lower extremities [2,25,26], fragments of the tibia [27] and the calcaneus [20,28].…”
Section: Introductionmentioning
confidence: 99%
“…This observation contradicted the results of Steele and McKern's [26] study. In addition to these two studies [25,26], other researchers have used measurements of the upper end of the radius and lower end of the femur [5] and segments of the ulna and tibia [27] in the estimation of the length of the respective bones.…”
Section: Introductionmentioning
confidence: 99%